COVID-19 and its effects: On the risk of social inequality through digitalization and the loss of trust in three European education systems. (September 2021) - Bormann, Inka; Brøgger, Katja; Pol, Milan; Lazarová, Bohumíra
This paper develops informed assumptions on the potential loss of trust as an unintended side-effect of the measures in education to contain the spread of the COVID-19 pandemic. Well-founded concerns according to which the pandemic-induced closure of educational facilities and the shift to digitalized distance education are contributing to increased social inequality in education serve as a starting point for the argumentation. The paper contends that together with the temporary changes in the style of educational governance, in the medium term an exacerbated social inequality in education can cause a potential trust problem for the central actors imposing the measures. To support this line of reasoning, the exploratory study describes the context conditions which are relevant for the implementation and participation in digitalized distance education (measures, access and competent use of digital devices in education, level of trust) and combines them with the findings of a qualitative analysis of relevant documents from three European countries (Czech Republic, Denmark, Germany). A neo-institutional view is applied to exploring the implications of the changes in education governance and their potential side-effects on trust.